The effectiveness of impulsive jet fans ventilation on CO concentration in closed car park - Mohaned Hossam Omar; Mahmoud Mohamed Kamal; Hamdy Ahmed Abotaleb (Engineering Applications of Computational Fluid Mechanics)
As there is a risk of CO contamination by vehicles running inside the car park. This research was initiated with the objective of assessing jet fans' impulsive ventilation “IV” performance and studying its effect on CO contamination in such garages, where a 1350 m2 UG (2.65 m high) was considered as a case study. 39 scenarios were proposed; visualized in a matrix, and simulated by a Computational Fluid Dynamics “CFD” model (ANSYS FLUENT 2019 R3), natural ventilation, and impulsive ventilation were studied. The proposed scenarios considered the jet fans “JFs” arrangement, in terms of number and interspacing and location within the garage, flow of JFs, and load capacity, in terms of the number of cars in operation. A code notation was made to describe each case's properties. The results highlighted valuable insights into the optimal arrangement of jet fans in UG. It flagged the importance of adjusting the number of fans, spacing, and location to attain reasonable ventilation performance. The research suggested implementing an inverter variable speed drive in the ventilation system to provide 6 or 10 ACH and adjusting them based on UG occupancy whether at normal load or peak load, Additionally, the On-Off system allows for the utilization of different arrangements according to the load requirements. A collective correlation was attempted to identify the values of CO in PPM according to load percentage and ACH.